Sintering of hydroxyapatite ceramic produced by wet chemical method - Singh, Ramesh; Ranna, Tolouei; Tan, Chou Yong; K. L., Aw; W., H. Yeo; Iis, Sopyan; Teng, Wan Dung (Trans Tech Publications, Switzerland, 2011)
In the present work, densification of synthesised hydroxyapatite (HA) bioceramic prepared via chemical precipitation method was investigated. HA samples was prepared by compaction at 200 MPa and sintered at temperatures ranging from 800°C to 1400°C. The results revealed that the HA phase was stable for up to sintering temperature of 1250°C. However, decomposition of HA was observed in samples sintered at 1300°C with the formation of tetra-calcium phosphate (TTCP) and CaO. Samples sintered above 1400°C were found to melt into glassy phases. The bulk density increases with increasing temperature and attained a maximum value of 3.14 gcm-3 at 1150°C whereas maximum hardness value of 6.64 GPa was measured in HA sintered at 1050°C. These results are discussed in terms of the role of grain size. © (2011) Trans Tech Publications, Switzerland.